Modeling of competence as a tool of goal setting for education in modern society - Yarygin O.N.; Korostelev A.A.; Akhmetov L.G.; Maseleno A. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
The purpose of this article is to examine problems related to the role of the educational system in the development of society, with the objectives of modern education in preparation for professional performance. Authors have analyzed the competence-based approach in education. They propose original structural and mathematical model of intellectual competence, methods for its evaluation and presenting its profile. The authors conclude that the purpose of education in modern society is to shape humanistic motivated competent individual. BEIESP.